PENGARUH BAKTERI PELARUT FOSPAT TERHADAP KETERSEDIAAN FOSPAT DAN PERTUMBUHAN TANAMAN - Ida Nursanti (Universitas Batanghari Jambi, 2008)
Soil has runs out of phosphore.Moreover, P fertilizing is inefficient because the P compound to be absorved by plants is bound to the other compound. Consequently, it is suggested that farmers use phosphate solvent microba such as phosphate solvent bacteria. As biofertilizer, phosphate solvent bacteria may function as a provider of P substance and soil arranger,besides, it is enviroment-friendly. Several types of phosphate solvent bacteria that significantly provide P substance and support the growth of plants are pseudomonas, bacillus,bacterium, citribacter and escherrechia.